The Role of Tenascin-C in Hypertrophic Scar Formation: Insights From Cell and Animal Experiments [Retraction] - Xiang W; Guo Z; Zhang Y; Xu Y (Clinical, Cosmetic and Investigational Dermatology, 2025)
Xiang W, Guo Z, Zhang Y, Xu Y. Clin Cosmet Investig Dermatol. 2024;17:1637—1648. We, the Editors and Publisher of the journal Clinical, Cosmetic and Investigational Dermatology, have retracted the published article. After publication, concerns have been raised by a third party about the integrity of the data in the article. Further investigations conducted by the Journal and Publisher confirmed duplicate image panels representative of different treatment conditions present in Figure 4 and Figure 5 of the article. When approached for an explanation, the authors responded and have provided their original data. However, further review by the Journal and Publisher identified additional data integrity concerns present in the original data. As verifying the validity of published work is core to the integrity of the scholarly record, we are therefore retracting the article. The corresponding author listed in this publication has been informed. We have been informed in our decision-making by our editorial policies and the COPE guidelines. The retracted article will remain online to maintain the scholarly record, but it will be digitally watermarked on each page as ‘Retracted’.